2018
DOI: 10.1111/jocd.12827
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling by dermapen and glycolic acid peel for the treatment of acne scars: Comparative study

Abstract: Summary Background Many methods have been performed to achieve a satisfying outcome in acne scars but some of them were high cost and also were associated with low results and some complications. Objectives To evaluate and compare the efficacy and safety therapy of glycolic acid (GA) peel, microneedling with dermapen and a combination of both procedures in treatment of atrophic acne scars. Patents and methods This study was conducted on 30 patients suffering from acne scars. They were randomly assigned into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
(19 reference statements)
1
17
0
2
Order By: Relevance
“…Results showed overall statistically significant improvement in acne scarring in all three groups (P<0.05). This study also showed statistically significant increase in frequency of very good satisfactory and objective rate in Group III compared to Groups I and II, and in Group I compared to Group II (P<0.05) [6].…”
Section: Acne Scarsupporting
confidence: 64%
“…Results showed overall statistically significant improvement in acne scarring in all three groups (P<0.05). This study also showed statistically significant increase in frequency of very good satisfactory and objective rate in Group III compared to Groups I and II, and in Group I compared to Group II (P<0.05) [6].…”
Section: Acne Scarsupporting
confidence: 64%
“…Studies that only used the PROM as an outcome measurement instrument were excluded, but study details were tabulated, per protocol. We identified 188 studies that reported treatment satisfaction as an outcome: 91 on treatment of acne 68–158 and 97 on treating acne scars (a possible sequela of acne) 159–255 . These numbers show that clinicians and researchers do consider treatment satisfaction as an important outcome.…”
Section: Resultsmentioning
confidence: 99%
“…A comparative study conducted between microneedling by Dermapen versus GA peel versus the combination of both suggests combination to be more effective. [ 34 ]…”
Section: Icroneedlingmentioning
confidence: 99%